2016
DOI: 10.1111/head.12840
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of Internet and Mobile Use on Headache and Other Somatic Symptoms in Adolescence. A Population‐Based Cross‐Sectional Study

Abstract: Results highlighted the potential impact of excessive internet and mobile use, which ranges from different types of headache to other somatic symptoms. Further studies are needed to confirm these findings and to determine if there is a need for promoting preventive health interventions, especially in school setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 38 publications
2
52
1
7
Order By: Relevance
“…Based on the search parameters, two studies were identified in this review (each cross‐sectional in design). Both studies (Cerutti et al, ; Milde‐Busch et al, ), found no significant relationship between phone use and reports of headaches and migraines.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Based on the search parameters, two studies were identified in this review (each cross‐sectional in design). Both studies (Cerutti et al, ; Milde‐Busch et al, ), found no significant relationship between phone use and reports of headaches and migraines.…”
Section: Resultsmentioning
confidence: 95%
“…Headaches and migraines . To date, much of the research on the effects of phone use on headaches and migraine prevalence has been conducted with adults (Cerutti, Presaghi, Spensieri, Valastro, & Guidetti, ). Based on the search parameters, two studies were identified in this review (each cross‐sectional in design).…”
Section: Resultsmentioning
confidence: 99%
“…Studies support these results and demonstrate that there is a significant correlation between the mental health and Internet usage (Choi, Park, & Cha, ; Lai et al, ; Ying & Zhang, ). In the previous studies, excessive Internet use of adolescents was found to be associated with depression (Ho et al, ), hostility (Alpaslan, Avcı, Soylu & Guzel, ), anxiety (Ho et al, ), somatization (Cerutti, Presaghi, Spensieri, Valastro, & Guidetti, ), attention‐deficit hyperactivity disorder (Yen, Ko, Yen, Wu, & Yang, ), and suicidal ideation (Alpaslan et al, ; I. H. Lin et al, ). Messias, Castro, Saini, Usman, and Peeples () found that the sadness, suicidal ideation, and suicide attempts of young people were significantly higher in adolescents who played Internet or video games for 5 hr or more in a day.…”
Section: Discussionmentioning
confidence: 94%
“…In the past decade, mobile phone use has become increasingly common in daily life. Mobile phone helps people maintain social network, but its excessive use is associated with negative health issues, such as mobile phone addiction (MPA) and related somatic and psychological problems …”
Section: Introductionmentioning
confidence: 99%